Isolasi dan Identifikasi Bakteri Selulolitik pada Buah Kopi Arabika (Coffea arabica L.) - Nona Au Waling; Made Sritamin; I Nyoman Wijaya (Fakultas Pertanian, Universitas Udayana, 2021)
Cellulolytic bacteria are microorganisms that can produce cellulase enzymes. Cellulolytic bacteria contain cellulase enzymes that play a role in the cellulose degradation processes. The purpose of this study was to isolate cellulolytic bacteria that capable to degrading cellulose from arabica coffee cherries collected from Catur Village, Kintamani. The results of bacterial isolation at 10-6 and 10-8 dilutions obtained 10 bacterial colonies. From the results of bacterial purification, 4 different bacterial isolates had different morphological characters. The results of the isolation of the colonies showed differences in a round and irregular shape, had raised and convex surfaces had red, cream, white and yellow colors, had curved and smooth edges. Tests were carried out on four bacterial isolates to determine the clear zone index. Only the L isolate in the congo red test had a diameter of clear zone 2.5 mm and with score 3 based on cellulolytic index value L isolate categorized as strong degrading cellulose bacteria.